2007
DOI: 10.1007/s11136-007-9192-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life outcome after hallux valgus surgery

Abstract: Hallux valgus patients have worse pain than the general population. Surgery produces a significant improvement in the quality of life. The severity of the deformity did not influence the QoL, however; the free choice of shoeware and the degree of satisfaction with the surgery had a positive effect on the QoL outcome. SF-36 is a relevant tool for evaluating outcome in hallux valgus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
4
21

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 23 publications
(24 reference statements)
5
71
4
21
Order By: Relevance
“…Three previous studies have examined the relationship between hallux valgus and the SF-36 (22)(23)(24); however, all 3 were conducted in hospital settings, and 2 used dichotomized definitions of hallux valgus (23,24). More recently, Abhishek et al reported that hallux valgus and concurrent big toe pain, but not hallux valgus alone, was associated with lower scores on the World Health Organization quality of life instrument (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three previous studies have examined the relationship between hallux valgus and the SF-36 (22)(23)(24); however, all 3 were conducted in hospital settings, and 2 used dichotomized definitions of hallux valgus (23,24). More recently, Abhishek et al reported that hallux valgus and concurrent big toe pain, but not hallux valgus alone, was associated with lower scores on the World Health Organization quality of life instrument (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although medical-grade footwear with additional width and depth to accommodate the deformity is now widely available, it has been suggested that these shoes may have a detrimental effect on self-esteem and therefore contribute to social isolation, particularly in older women (40,41). Indeed, in patients considering surgical correction of hallux valgus, the ability to wear regular footwear is one of the most frequently cited expectations of the surgery (42), and satisfaction following surgery is strongly influenced by whether or not patients are able to wear their preferred footwear (24,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saro ve arkadaşlarının 94 HV'lu kadın üzerinde yaptıkları çalışmada genel popülasyonla karşılaştırıldığında bireylerin yaşam kalitelerinin daha düşük olduğu, açısal şiddetle SF-36 ve AOFAS-MTF-IP skorları arasında herhangi bir ilişki olmadığı tespit edilmiştir. Bu çalışmada cerrahi girişimden SF-36 skorlarında belirgin düzelme olduğu saptanmıştır (18). Bu çalışmadaki sonuçlara benzer olarak Thordarson genel poülasyonla karşılaştırıldığında HV'lu hastaların SF-36-ağrı alt skalası değerlerinin daha düşük olduğunu rapor etmiştir (17).…”
Section: Discussionunclassified
“…Deformitenin denge, yürüyüş ve ağırlık aktarımını olumsuz yönde etkilediği ve yaşlılarda düşme riskini artırdığı rapor edilmiştir (14,15). Bazı çalışmalarda HV deformitesinin sağlıkla ilgili yaşam kalitesi üzerine olumsuz etkileri olduğu gösterilmiştir (16)(17)(18). Bu çalışmanın amacı HV deformitesinin açısal şiddetinin genel ve ayağa özel sağlıkla ilgili yaşam kalitesi üzerine etkisini incelemekti.…”
Section: Introductionunclassified